2020
DOI: 10.31219/osf.io/gfej2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Responsive Leadership in Preventing Transmission of Covid-19 in the Indonesia-Malaysia Border Area

Abstract: The spread of the COVID-19 is increasingly globalized to have an impact not only on human health but also on all lines of life that requires rapid responses with anticipatory and preventive steps before its effects become worse. All countries feel the impact of outbreak, which moves so fast, including border communities. Today, COVID-19 travels through the human respiratory system to one another and from one area to another including Sambas area. The purpose of this study was to investigate the leadership resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Leaders who are able to transform are expected to guide employees in dealing with environmental changes, increase motivation, and optimize overall performance. Leader effectiveness in communication is a key factor influencing employee performance (Obi, 2018;Oskar Hutagaluh et al, 2020;Saad et al, 2018). Similarly, transformational leadership was shown to have a significant effect on team decisionmaking, which in turn led to improved employee performance (Dionne et al, 2004;Jung & Sosik, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Leaders who are able to transform are expected to guide employees in dealing with environmental changes, increase motivation, and optimize overall performance. Leader effectiveness in communication is a key factor influencing employee performance (Obi, 2018;Oskar Hutagaluh et al, 2020;Saad et al, 2018). Similarly, transformational leadership was shown to have a significant effect on team decisionmaking, which in turn led to improved employee performance (Dionne et al, 2004;Jung & Sosik, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Populism is a "thin ideology" with two components: the idea of a good people pitted against a corrupt elite; and the belief that politics should be an expression of the will of the people [12]. Since the COVID-19 pandemic spread in Indonesia, the studies on how populist leaders respond to the global pandemic have increasingly shown positive growth [13]- [15], including some studies related to populist local leaders' actions during the pandemic [16], [17], which explains how local leaders are utilizing crises to build their electability. On a national level, some political scholars also discuss Jokowi's populist leadership and his failure to handle the crisis [18], [19].…”
Section: Introductionmentioning
confidence: 99%